Origins, identification and type status of two early specimens of Society Kingfisher Todiramphus veneratus (J. F. Gmelin, 1788) (Aves: Coraciiformes, Alcedinidae) - van Der Vliet, Roland E.; Cibois, Alice; Gamauf, Anita; Jansen, Justin J.f.j. (Zootaxa, 2019)
We re-examined the putative type specimen of Society Kingfisher Todiramphus veneratus (J. F. Gmelin, 1788) in the Naturhistorisches Museum Wien (NMW 50.633) and conclude based on plumage that it represents the taxon from Moorea, T. veneratus youngi Sharpe, 1892, rather than nominate T. veneratus veneratus from Tahiti. X-rays reveal that it was prepared using techniques common in the late 18th century, and that its preparation style matches that of other specimens collected during Cook’s three voyages. NMW 50.633 has been assumed to be the one, or one of a number of, specimen(s) used by Latham to describe and illustrate his ‘Venerated Kingfisher’ (present-day Society Kingfisher), which was the basis of the later valid introduction of the name Alcedo venerata by J. F. Gmelin. However, whereas the description and an unpublished illustration in Latham’s archives agree closely with veneratus from Tahiti, NMW 50.633 appears to represent Moorea youngi. While this finding does not compromise the definition of Society Kingfisher veneratus, it leaves it without a safely identified type specimen. We also examined a Moorea specimen in the National Museums Liverpool (LIVCM D2366) that is almost as old as NMW 50.633, but which X-rays suggest had a different origin than NMW 50.633.